Tricentennial trends in spring ice break-ups on three rivers in northern Europe - Norrgård, Stefan; Helama, Samuli (The Cryosphere, 2022)
At high latitudes, long-term changes in riverine ice break-ups are exemplary measures of climatic change and variation. This study compares cryophenological trends, patterns and changes for the rivers Aura (1749–2020), Torne (1693–2020) and Kokemäki (1793–2020); all sites are located in Finland. The Kokemäki River series is a new series from the city of Pori. The findings show statistically significant cross-correlations between the Aura and Kokemäki rivers but weaker cross-correlations with the Torne River. We attribute the latter to climatic differences caused by the higher latitude of the Torne River. Taken together, the many results of this study suggest that the spring climate in the south has changed more rapidly and become less predictable than in the north. Climatic extremes – warmer and wetter winters – in the 2000s resulted in the first recorded no-freeze events on the Aura and Kokemäki rivers. This was the culmination of a rapid increase in early ice break-up events and interannual variability over the last 30 years. The number of early events has increased in all three rivers since the early or mid-1900s, but the earliest recorded break-up day on the Torne River has changed only marginally in the last 100 years. Our dynamic temperature analysis shows that the ice break-up on the Torne River requires higher temperatures than in the south, and future changes in the timing of the break-up depend on April temperatures. In the south, on the other hand, future changes concerns the return period of no-freeze events, which depend on temperature and precipitation during winter.